Kekerabatan Bahasa Alunedan Bahasa Wemale - Simon, Johana Grace (Kajian Linguistik, 2015)
This research isbased on Comparative Historical Linguistics study. It is motivated by thesimilarity of phonology and lexicon in Alune and Wemale languages, thelanguages are almost extinct, and there is no research about the relationshipof these languages before.The methods usedare Quantitative and Qualitative. The technique for Quantitative islexicostatistics and the technique for Qualitative is reconstruction of protolanguage. The sources of data are taken from the informants, texts, and SwadeshÂ  words list.In this research, it is found that there are 94related words, consisting of 33 words with exactly the same phonemes and 61words having resemblance in phonology and lexicon. Meanwhile, there are 105different basic vocabularies. It is also found that Alune and Wemale languagesare related in the level of family. Furthermore, there are 18 reconstructed protophonemes and 94 proto etimons.Keywords:Lexicostatistics, reconstruction.